Implementasi Pembelajaran Tahsin Melalui Metode Iqra’ dalam Meningkatkan Kefasihan Bacaan Al-Qur’an Siswa Pas Java Desa Saentis - Dzul Padli; Abdi Syahrial Harahap; Nanda Rahayu Agustia (Medan Resource Center, 2025)
This study aims to analyze the implementation of tahsin learning using the Iqra’ method in improving the fluency of Al-Qur’an reading among students at Pas Java, Saentis Village. The study is grounded in the need for effective and structured approaches to enhance students’ ability to read the Al-Qur’an correctly in accordance with tajwid principles. A descriptive qualitative method was employed, with data collected through observations, in-depth interviews, and documentation involving teachers and students at Pas Java. The findings indicate that the Iqra’ method significantly improves students’ reading fluency, particularly in recognizing hijaiyah letters, applying harakat accurately, and reading the Al-Qur’an in a tartil manner. This improvement is supported by the systematic structure of the six Iqra’ volumes, the application of the CBSA (Active Student Learning) approach, and the use of an intensive mentoring system. However, the study also identifies students limited initial knowledge of hijaiyah letters as a major challenge, which can be effectively addressed through gradual learning stages and continuous guidance. This study contributes to the development of tahsin learning by providing empirical evidence on the effectiveness of the Iqra’ method as a structured and adaptive instructional model that can be applied in non-formal Qur’anic education settings.